2019
DOI: 10.12659/msm.913368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclocarya Paliurus on Hypoglycemic Effect in Type 2 Diabetic Mice

Abstract: Background The aim of this study was to assess the hypoglycemic effect of Cyclocarya paliurus extract (CPE) on diabetes mellitus (DM) mice. Material/Methods A DM mouse model was established to test FBG, TC, and TG. The DM mice were divided into 3 groups: a DM group, a DM+CPE (0.5 g/Kg) group, and a DM+CPE (1.0 g/Kg) group. The FBG and body weight were measured. The glucose tolerance ability was determined by OGTT test. FINS was measured to cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…In animal studies, CP was shown to decrease pancreatic β cell apoptosis, possibly due to the regulation of mitogen-activated protein kinase (MAPK) pathways and Akt pathways (9). Furthermore, restoration of β cell mass and function were found in histological observations, moreover, this β-cell-protecting effect was also confirmed by in vitro studies in NIT-1 cells (8,9), which are a pancreatic β cell line established from mice (50).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In animal studies, CP was shown to decrease pancreatic β cell apoptosis, possibly due to the regulation of mitogen-activated protein kinase (MAPK) pathways and Akt pathways (9). Furthermore, restoration of β cell mass and function were found in histological observations, moreover, this β-cell-protecting effect was also confirmed by in vitro studies in NIT-1 cells (8,9), which are a pancreatic β cell line established from mice (50).…”
Section: Discussionmentioning
confidence: 85%
“…Inflammatory cytokines like tumor necrosis factor-α (TNF-α) down-regulate the activation of insulin receptors (54), and eventually lead to insulin resistance, causing hypertriglyceridemia, low HDL levels and high LDL levels (55). In many current animal studies, CP administration successfully decreases the expression of TNFα, interleukin-6 (IL-6), malondialdehyde (MDA), and increases superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) levels, showing its capacity for controlling inflammation and oxidative stress (8,10,11,16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inhibition of NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) inflammasome activity led to the decrease in IL-1β expression, and regulated inducible nitric oxide synthase (iNOS), TNF-α, arginase 1 (Arg1), and IL-10. Zhao et al reported that after the administration of Cyclocarya paliurus extract for 4 weeks at doses of 0.5 and 1.0 g/kg, FBG, fasting insulin level and insulin resistance index (IRI) were reduced and insulin sensitivity index (ISI) was enhanced [ 90 ]. The downregulation of serum MDA content and the upregulation of antioxidant enzymes such as SOD and GSH-Px were also observed.…”
Section: Type 2 Diabetes and Plant Extractsmentioning
confidence: 99%